The Protective Effects of N-acetylcysteine against 5-Fluorouracil Induced Intestinal Toxicity in Albino Rats - Al-Hamdany, Muna; Al-Hubaity , Abduljabar (Iraqi Journal of Pharmaceutical Sciences, 2023)
5-fluorouracil (5-FU) is a is Pyrimidine analogue widely used in the treatment of various malignancies It belongs to the antimetabolites family that acts during the S-phase of the cell cycle thus it prevents DNA synthesis.N-acetylcysteine is nutritional complement acts as antioxidant.The purpose of the current study is to investigate whether there is a protective role of N-acetylcystein against intestinal toxicity induced by 5-fluorouracil in albino rats.18 healthy adult rats were distributed into 3 groups of 6 rats for each. Group A as a control group.Group B injected with 5-FU (20 mgs dissolved in 2ml normal saline per kilogram body weight intraperitoneally for 7 successive days while Group C received N-acetylcysteine 200 mg per kilogram body weight 24 hour prior to FU injections for 7 consecutive days. The animals were sacrificed specimens of intestine (colon) tissue of the three groups were removed and prepared for light microscopic examination.The sections were stained with Harris Hematoxylin and Eosin (H&E) stain and Masson’s trichrome stain. Results showed increase in the depth of the colonic crypts in group B rats as compared to the control group, mucinous degeneration of the intestinal mucosal cells along with necrosis, and inflammatory cells infiltration in the lamia propria. The appearance of the crypts is nearly normal in group C with reduction in the depth and normal columnar epithelium lining the crypts the study concluded that 5-FU seriously affects the structure of the intestinal tissue and pretreatment with NAC protects the intestinal tissue against the toxic effects provoked by 5FU via antioxidant effect.